Performance of ChatGPT in the Portuguese National Residency Access Examination - Gonçalo Ferraz-Costa; Mafalda Griné; Manuel Oliveira-Santos; Rogério Teixeira (Acta Médica Portuguesa)
ChatGPT, a language model developed by OpenAI, has been tested in several medical board examinations. This study aims to evaluate the performance of ChatGPT on the Portuguese National Residency Access Examination, a mandatory test for medical residency in Portugal. The study specifically compares the capabilities of ChatGPT versions 3.5 and 4o across five examination editions from 2019 to 2023. A total of 750 multiple-choice questions were submitted to both versions, and their answers were evaluated against the official responses. The findings revealed that ChatGPT 4o significantly outperformed ChatGPT 3.5, with a median examination score of 127 compared to 106 (p = 0.048). Notably, ChatGPT 4o achieved scores within the top 1% in two examination editions and exceeded the median performance of human candidates in all editions. Additionally, ChatGPT 4o’s scores were high enough to qualify for any specialty. In conclusion, ChatGPT 4o can be a valuable tool for medical education and decision-making, but human oversight remains essential to ensure safe and accurate clinical practice.